Study on preparation of chickpea peptide and its effect on blood glucose - Ma, Xuemei; Fan, Xing; Wang, Deping; Li, Xianai; Wang, Xiaoyun; Yang, Jiangyong; Qiu, Chenggong; Liu, Xiaolu; Pang, Guangxian; Abra, Redili; Wang, Liang (Frontiers in Nutrition, 2022)
Chickpea is the third largest bean in the world, which is rich in protein. In this study, chickpea peptides were prepared by enzyme bacteria synergy method. Taking the peptide yield as the index, we first screened 8 strains suitable for the fermentation of chickpea peptides from 16 strains, carried out sodium dodecyl sulfate polyacrylamide gel electrophoresis, and then screened 4 strains with the best decomposition effect of chickpea protein.The molecular weight, amino acid content and α-glucosidase inhibitory activity of the chickpea peptides fermented by these four strains were detected. Finally, the strains with the best α-glucosidase inhibitory activity were obtained, and the inhibitory activities of the different molecular weight components of the chickpea peptides fermented by the strains with the best α-glucosidase inhibitory were detected. It was found that Bifidobacterium species had the best fermentation effect, and the hightest peptide yield is 52.99±0.88%;Lactobacillus thermophilus had the worst fermentation effect, and the hightest peptide yield is 43.22±0.47%. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis showed that Bifidobacterium species, Lactobacillus acidophilus, Lactobacillus rhamnosus,